Association Between Bone Mineral Density and Autoantibodies in Patients With Rheumatoid Arthritis. Issue 6 (10th May 2021) - Amkreutz, Josephine A. M. P.; de Moel, Emma C.; Theander, Lisa; Willim, Minna; Heimans, Lotte; Nilsson, Jan‐Åke; Karlsson, Magnus K.; Huizinga, Tom W. J.; Åkesson, Kristina E.; Jacobsson, Lennart T. H.; Allaart, Cornelia F.; Turesson, Carl; et al.
Abstract : Objective: Autoantibodies, such as anti–citrullinated protein antibodies (ACPAs), have been described as inducing bone loss in rheumatoid arthritis (RA), which can also be reflected by bone mineral density (BMD). We therefore examined the association between osteoporosis and autoantibodies in two independent RA cohorts. Methods: Dual x‐ray absorptiometry (DXA) of the lumbar spine and left hip was performed in 408 Dutch patients with early RA during 5 years of follow‐up and in 198 Swedish patients with early RA during 10 years of follow‐up. The longitudinal effect of ACPAs and other autoantibodies on several BMD measures was assessed using generalized estimating equations. Results: In the Dutch cohort, significantly lower BMD at baseline was observed in ACPA‐positive patients compared to ACPA‐negative patients, with an estimated marginal mean BMD in the left hip of 0.92 g/cm 2 (95% confidence interval [95% CI] 0.91–0.93) versus 0.95 g/cm 2 (95% CI 0.93–0.97) ( P = 0.01). In line with this, significantly lower Z scores at baseline were noted in the ACPA‐positive group compared to the ACPA‐negative group (estimated marginal mean Z score in the left hip of 0.18 [95% CI 0.08–0.29] versus 0.48 [95% CI 0.33–0.63]) ( P < 0.01). However, despite clear differences at baseline, ACPA positivity was not associated with greater decrease in absolute BMD or Z scores over time. Furthermore, there was no association between BMD and higher levels of ACPAs or other autoantibodies (rheumatoid factor and anti–carbamylated protein antibodies). In the Swedish cohort, ACPA‐positive patients tended to have a higher prevalence of osteopenia at baseline ( P = 0.04), but again, ACPA positivity was not associated with an increased prevalence of osteopenia or osteoporosis over time. Conclusion: The presence of ACPAs is associated with significantly lower BMD at baseline, but not with greater BMD loss over time in treated RA patients. These results suggest that ACPAs alone do not appear to contribute to bone loss after disease onset when disease activity is well‐managed.